Foreign language comprehension achievement: insights from the cognate facilitation effect - Casaponsa, Aina; Antón, Eneko; Pérez, Alejandro; Duñabeitia, Jon A. (Frontiers in Psychology, 2015)
Numerous studies have shown that the native language influences foreign word recognition and that this influence is modulated by the proficiency in the nonnative language. Here we explored how the degree of reliance on cross-language similarity (as measured by the cognate facilitation effect) together with other domain-general cognitive factors contribute to reading comprehension achievement in a nonnative language at different stages of the learning process. We tested two groups of native speakers of Spanish learning English at elementary and intermediate levels in an academic context. A regression model approach showed that domain-general cognitive skills are good predictors of second language reading achievement independently of the level of proficiency. Critically, we found that individual differences in the degree of reliance on the native language predicted foreign language reading achievement, showing a markedly different pattern between proficiency groups. At lower levels of proficiency the cognate facilitation effect was positively related with reading achievement, while this relation became negative at intermediate levels of foreign language learning. We conclude that the link between native- and foreign-language lexical representations helps participants at initial stages of the learning process, whereas it is no longer the case at intermediate levels of proficiency, when reliance on cross-language similarity is inversely related to successful nonnative reading achievement. Thus, at intermediate levels of proficiency strong and direct mappings from the nonnative lexical forms to semantic concepts are needed to achieve good nonnative reading comprehension, in line with the premises of current models of bilingual lexico-semantic organization.